Acute Liver Failure Caused by Amanita phalloides Poisoning - Luca Santi; Caterina Maggioli; Marianna Mastroroberto; Manuel Tufoni; Lucia Napoli; Paolo Caraceni (International Journal of Hepatology)
Mushroom poisoning is a relatively rare cause of acute liver failure (ALF). The present paper analyzes the pathogenesis, clinical features, prognostic indicators, and therapeutic strategies of ALF secondary to ingestion of Amanita phalloides, which represents the most common and deadly cause of mushroom poisoning. Liver damage from Amanita phalloides is related to the amanitins, powerful toxins that inhibit RNA polymerase II resulting in a deficient protein synthesis and cell necrosis. After an asymptomatic lag phase, the clinical picture is characterized by gastrointestinal symptoms, followed by the liver and kidney involvement. Amatoxin poisoning may progress into ALF and eventually death if liver transplantation is not performed. The mortality rate after Amanita phalloides poisoning ranges from 10 to 20%. The management of amatoxin poisoning consists of preliminary medical care, supportive measures, detoxification therapies, and orthotopic liver transplantation. The clinical efficacy of any modality of treatment is difficult to demonstrate since randomized, controlled clinical trials have not been reported. The use of extracorporeal liver assist devices as well as auxiliary liver transplantation may represent additional therapeutic options.